1990
DOI: 10.1007/bf01868674
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the gap junction protein connexin43 in embryonic chick lens: Molecular cloning, ultrastructural localization, and post-translational phosphorylation

Abstract: Lens epithelial cells are physiologically coupled to each other and to the lens fibers by an extensive network of intercellular gap junctions. In the rat, the epithelial-epithelial junctions appear to contain connexin43, a member of the connexin family of gap junction proteins. Limitations on the use of rodent lenses for the study of gap junction formation and regulation led us to examine the expression of connexin43 in embryonic chick lenses. We report here that chick connexin43 is remarkably similar to its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
183
0
11

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(202 citation statements)
references
References 45 publications
8
183
0
11
Order By: Relevance
“…Is Phosphorylated by CK1␦ in Vitro and in Cell Culture-Several studies have shown that Cx43 is phosphorylated on multiple different serine residues throughout its life cycle in homeostatic cells (12,33,34). Many kinases including CK1 are thought to remain constitutively active in cells and could phosphorylate Cx43 in the absence of exogenous kinase stimulation.…”
Section: Cx43mentioning
confidence: 99%
“…Is Phosphorylated by CK1␦ in Vitro and in Cell Culture-Several studies have shown that Cx43 is phosphorylated on multiple different serine residues throughout its life cycle in homeostatic cells (12,33,34). Many kinases including CK1 are thought to remain constitutively active in cells and could phosphorylate Cx43 in the absence of exogenous kinase stimulation.…”
Section: Cx43mentioning
confidence: 99%
“…Unlike many other membrane proteins, connexins are relatively dynamic, for pulse-chase assays had demonstrated that most connexins have half-lives of 1-3 h in cultured cells [12][13][14][15]. Turnover, degradation, and remodeling of gap junctions may contribute substantially to the regulation of intercellular communication [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Cx46 and Cx50 are mainly expressed in the lens fiber cells (Paul et al, 1991;White et al, 1992), whereas Cx43 is restricted to the anterior lens epithelium (Yancey et al, 1992). The chicken orthologues of these connexins have been identified as Cx56, Cx45.6, and Cx43 (Musil et al, 1990;Rup et al, 1993;Jiang et al, 1994). Both Cx46 and Cx50 knockout mice developed cataracts (Gong et al, 1997;White et al, 1998), indicating the importance of gap junctions in the maintenance of lens fiber homeostasis in mammals.…”
Section: Introductionmentioning
confidence: 99%